Methodology for estimation of meat production in North-East Hilly Region - GUPTA, A K; CHANDRA, HUKUM; SUD, U C; SINGH, MAN (The Indian Journal of Animal Sciences, 2014)
This article describes an alternative sampling methodology for estimation of meat production in North-East Hilly region, where existing approach leads to underestimation in meat production. The proposed methodology was implemented in East Khasi Hills district of Meghalaya to estimate the species-wise number of animals slaughtered and meat production from different sources. The estimates generated from the proposed approach were more realistic than the existing methodology.